Ride-through of Offshore Wind Parks - Enquist, Johan (My University, 2007)
Wind power has proven to be a good alternative in the quest for renewable energy sources. One way to increase the efficiency is to construct large wind parks situated at sea. At the time of writing, wind parks containing more than a hundred wind turbines with a capacity of several hundred megawatts are being planned. Since wind turbines are rather sensitive to reduction in the system voltage, protection devices might disconnect the park from the grid when exposed to a voltage dip. Loosing a large generating unit like a large wind park may lead to instability problems. To prevent this, many system operators have started to include so-called ride-through requirements in their grid codes. This thesis presents an overview and comparison of a number of grid codes. Most of the ride-through requirements apply to the connection point of the whole wind park which makes it difficult to know how the voltage dip requirement actually looks like at the wind turbine terminals. The voltage dip profiles have therefore been “translated” to the wind turbine terminals. The impact on these requirements with different power system grounding methods as well as transformer winding connections has also been analyzed in the report.
Keywords: Elkraftteknik; Electric power engineering